PENGARUH MASA PENUGASAN AUDIT DAN SPESIALISASI KAP TERHADAP KUALITAS AUDIT - SUATU STUDI DENGAN PENDEKATAN EARNINGS SURPRISE BENCHMARK - Muhammad Iqbal; Indira Januarti (Diponegoro Journal of Accounting, 2015)
This study examines the effects of past audits and the Firm specializes in audit quality approaches benchmark earnings surprise. This study shows how the independent variable that are past audist and firm specializes can prove that the dependent variable which iss audit quality identified as having an effect between earnings management with audit quality of financial statements. Proxy that used in this study is net income with total assets and how to compare them by comparing the percentage of the the following proxy with percentage of the difference from the previous year's net income and earnings in the previous year observations with assets.Populations in this study are all companies listed in Indonesia Stock Exchange in the period 2010 - 2012. Sampling was done in accordance with previous studies of Simnett and Carey (2006), namely with certain criteria so that samples obtained for this study amounted to 120 companies. The analysis method of this research is using logistic regression method.Based on the results of the study shows that the duration of the audit assignment was not significant and has negative impact as well as specialization KAP not significant and has negative impact on audit quality.